Recombinant protein application induced defense mechanism in host plant against papaya dieback disease - Bakar, Ros Azrinawati Hana; Abu Bakar, Norliza; Ahmad, Khairulmazmi; Shaharuddin, Noor Azmi; Abdul Wahab, Mohd As’wad; Juri, Nor Mustaiqazah (Penerbit Universiti Teknologi Malaysia, 2023)
Erwinia mallotivora is a Gram-negative bacterium that causes the papaya dieback disease in Malaysia. Currently, no effective disease control method is documented. In this regard, the adoption of harpin proteins in promoting plant defense mechanisms has been reported to be a promising control method for this disease. This study used, two recombinant harpin proteins, Hrp I and Hrp II, to control the disease in the glasshouse and field conditions. The results of foliar application in the glasshouse showed protective index of 70.8% and 35.7% for Hrp I and Hrp II, respectively. Meanwhile, the field trial for Hrp I showed a promising protection index of 72.3%. Moreover, the plant growth-promoting attributes were also significantly improved in the case of the Hrp I -treated plants. The effectiveness of Hrp I and II as inducers of systemic acquired resistance (SAR) was further validated by profiling defense-related genes using RT-qPCR analysis. The results showed that the treated papaya plants with Hrp I possess the highest expression of defense genes such as peroxidase, osmotin, and PRID in the glasshouse and field samples. In conclusion, the application of Hrp I is a promising disease control approach in managing papaya dieback disease in Malaysia.